Off-label use of atomoxetine in adults: is it safe? - Dadashova, Rana (Ment Illn, 2012)
Atomoxetine has been approved for the treatment of attention deficit/hyperactivity disorder in both adults and children. However, it is also being examined for several off-label uses in adults including mood disorders, eating disorders, cognitive dysfunction, and the treatment of addictions. Prior to such use it is important to examine the reported adverse events to see if this represents an appropriate level of risk. This is particularly important in the light of recent warnings from several regulatory bodies about an increase in blood pressure in a significant percentage of patients taking atomoxetine. To understand the risks a literature review was performed, and which identified the following potential problems. The first is that this drug should not be given in patients with known cardiovascular problems, and that all adult patients who receive atomoxetine should be monitored for changes in blood pressure throughout treatment. Secondly, there are several clinical situations in which atomoxetine should be closely monitored, or avoided, including patients who have a history or risk of narrow angle glaucoma, epileptic seizures, Tourette's syndrome, a history of urinary outflow obstruction, or who are pregnant or lactating. In conclusion, the current literature suggests that atomoxetine can be safely used off-label provided the above precautions are taken.